Design and Development of Soap Herbal Tablet of Larrea divaricata (Cav.) with Antifungal Activity Against Candida albicans - Jofre, Maria de Los Angeles (2024)
In this present work soap herbal tablet of Larrea divaricata Cav. ethanolic extract (LdE) with antifungal activity against Candida albicans, was designed and developed. The chemical profile of main compounds and quantification of nordihydroguaiaretic acid (NDGA) in the LdE was performed by means of UPLC-MS/MS. Two formulations (F1 and F2) were prepared by direct compression with different concentrations of active herbal ingredient (AHI). The performance of three carriers for impregnating LdE was evaluated. TRI-CAFOS® 500 was selected as carrier after a comparative study by Scanning Electron Microscope with AEROSIL® 200 and AEROPERL® 300. StarLac® 90, a coprocessed lactose, was employed as binder. The soap herbal tablets quality parameters were evaluated in accordance with United States Pharmacopeia (USP-43) guidelines, weight variation, hardness, friability, disintegration test, foam stability test and microbiological assay against candida albicans were performed. The F1 (LdE + TRI-CAFOS®500 (LdET1) 62.8%, StarLac®90 0.1%, Microcrystalline cellulose 10%, vitamin E 0.1%, Betan F® 5%, Lactic acid 5%, Rose essence 0.1%, Low density Hyaluronic acid 1.5% and magnesium stearate 0.5%) showed optimal rheological properties, good biopharmaceutical parameters (Disintegration test (27.33s), Hardness (3.00Kp), Friability (0.92%), Foam stability (1.12)) and Minimum inhibitory concentration (MIC) 25 mg/ml for Candida albicans. Considering that there are no soap herbal tablets on the market, the present design can be used as a novel herbal cosmetic form of vaginal hygiene.